PROBLEMATIKA HUKUM SUBSTANSI SURAT EDARAN MAHKAMAH AGUNG NOMOR 2 TAHUN 2019 SEBAGAI DASAR HUKUM PENGAJUAN KEPAILITAN BURUH - Putri, Clarisa Permata Hariono (Legal Standing : Jurnal Ilmu Hukum, 2024)
Factually, there is a dualism in the judge's decisions responding to bankruptcy applications by workers, so that the Supreme Court Circular Letter Number 2 of 2019 was formed. This research aims to analyze the existence of legal problems in terms of substance in the Supreme Court Circular Letter Number 2 of 2019. This legal research is normative legal research with statutory and conceptual approaches. The results of the research concluded that there are several legal problems on the Supreme Court Circular, including the incompatibility of the concept of bankruptcy with the provisions of legislation in the field of bankruptcy, provisions that conflict with the absolute authority of the Industrial Relations Court and the Commercial Court, and the existence of a legal vacuum in the provisions of Supreme Court Circular Letter Number 2 of 2019.